PEMIKIRAN PENDIDIKAN ISLAM PERSPEKTIF ULAMA NUSANTARA KH. HASYIM ASY-ARI DAN KH. ACHMAD DAHLAN - Ruslan; Zainuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and compare the Islamic educational thoughts of KH. Hasyim Asy’ari and KH. Ahmad Dahlan, focusing on educational objectives, methods, curriculum, and their relevance to modern Islamic education. The research employs a qualitative method using a library research approach, supported by historical-philosophical and comparative approaches. Data were collected from primary sources, including the works of both figures, and secondary sources such as books, journals, and scholarly articles, which were analyzed through data reduction, data display, comparative analysis, and conclusion drawing. The findings reveal that KH. Hasyim Asy’ari emphasized education based on adab (ethics), morality, and spirituality through the pesantren tradition, while KH. Ahmad Dahlan developed a modern educational model integrating religious and general sciences with a focus on social reform. Both figures shared the view that education serves as a means of moral formation and community empowerment based on the Qur’an and Sunnah. Their differing perspectives complement one another and remain relevant as a foundation for developing a holistic, moderate, and adaptive model of Islamic education in response to contemporary challenges.